Nanomedicine: The new trend and future of precision medicine for inflammatory bowel disease - Huanyu Li; Meng Pan; Yifan Li; Hao Liang; Manli Cui; Mingzhen Zhang; Mingxin Zhang; Yuanyuan Ji (Chinese Medical Journal)
Abstract. Nanomedicine is an interdisciplinary area that utilizes nanoscience and technology in the realm of medicine. Rapid advances in science and technology have propelled the medical sector into a new era. The most commonly used nanotechnology in the field of medicine is nanoparticles. Due to their unique physicochemical properties, nanoparticles offer significant benefits of precision medicine for diseases such as inflammatory bowel disease that cannot be effectively treated by existing approaches. Nanomedicine has emerged as a highly active research field, with extensive scientific and technological studies being carried out, as well as growing international competition in the commercialization of this field. The accumulation of expertise in the key technologies relating to nanomedicine would provide strategic advantages in the development of cutting-edge medical techniques. This review presented a comprehensive analysis of the primary uses of nanoparticles in medicine, including recent advances in their application for the diagnosis and treatment of inflammatory bowel disease. Furthermore, we discussed the challenges and possibilities associated with the application of nanoparticles in clinical settings.